El tiempo debe detenerse - Huxley, Aldous, 1894-1963 (Pocket Edhasa., 2013)
Sebastian Barnack, a handsome English schoolboy, goes to Italy for the summer, and there his real education begins. His teachers are two quite different men: Bruno Rontini, the saintly bookseller, who teaches him about things spiritual; and Uncle Eustace, who introduces him to life's profane pleasures.